It is currently 09 Apr 2020, 23:59

### GMAT Club Daily Prep

#### Thank you for using the timer - this advanced tool can estimate your performance and suggest more practice questions. We have subscribed you to Daily Prep Questions via email.

Customized
for You

we will pick new questions that match your level based on your Timer History

Track

every week, we’ll send you an estimated GMAT score based on your performance

Practice
Pays

we will pick new questions that match your level based on your Timer History

# If 6x - 4 = 5x + 3, then x = (A) -7 (B) -1 (C) 1 (D) 7 (E)

Author Message
TAGS:
Founder
Joined: 18 Apr 2015
Posts: 10225
Followers: 212

Kudos [?]: 2544 [0], given: 9586

If 6x - 4 = 5x + 3, then x = (A) -7 (B) -1 (C) 1 (D) 7 (E) [#permalink]  08 Mar 2020, 10:58
Expert's post
00:00

Question Stats:

100% (00:09) correct 0% (00:00) wrong based on 6 sessions
If 6x - 4 = 5x + 3, then x =

(A) -7

(B) -1

(C) 1

(D) 7

(E) 12

Kudos for the right answer and explanation
[Reveal] Spoiler: OA

_________________

Need Practice? 20 Free GRE Quant Tests available for free with 20 Kudos
GRE Prep Club Members of the Month: Each member of the month will get three months free access of GRE Prep Club tests.

GRE Instructor
Joined: 10 Apr 2015
Posts: 3006
Followers: 112

Kudos [?]: 3303 [1] , given: 56

Re: If 6x - 4 = 5x + 3, then x = (A) -7 (B) -1 (C) 1 (D) 7 (E) [#permalink]  26 Mar 2020, 09:25
1
KUDOS
Expert's post
Carcass wrote:
If 6x - 4 = 5x + 3, then x =

(A) -7
(B) -1
(C) 1
(D) 7
(E) 12

Given: 6x - 4 = 5x + 3
Subtract 5x from both sides: x - 4 = 3
Add 4 to both sides: x = 7

ASIDE: Although this equation is relatively easy to solve, a sure-fire approach to solving questions like this is to test each answer choice to see which one satisfies the given equation.

Cheers,
Brent
_________________

Brent Hanneson – Creator of greenlighttestprep.com

Re: If 6x - 4 = 5x + 3, then x = (A) -7 (B) -1 (C) 1 (D) 7 (E)   [#permalink] 26 Mar 2020, 09:25
Display posts from previous: Sort by